Pengaruh Kualitas Pelayanan Dan Harga Terhadap Kepuasan Pelanggan Counter Farah Cell - Siti Diana Faradisa; Amin Sadiqin (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2021)
A company is required to be able to maintain a good name in the eyes of its customers. Whether in terms of service or price. Good and friendly service will increase the number of buyers, making it easier for the company to achieve its goal of getting maximum profit. Not only that, but price also has a significant influence on customer satisfaction. Low prices can attract customers to buy what the company sells. This journal will discuss the effect of service quality and price on customer satisfaction using a descriptive type of research, using a qualitative approach. The results showed that there was a positive and significant influence between product quality and price on customer satisfaction.